Effect of Modulating DLPFC Activity on Antisocial and Prosocial Behavior: Evidence From a tDCS Study - Zheng, Wanjun; Li, Yuzhen; Ye, Hang; Luo, Jun (Frontiers in Psychology, 2021)
Antisocial behavior and prosocial behavior in the condition of inequality have long been observed in daily life. Understanding the neurological mechanisms and brain regions associated with antisocial and prosocial behavior and the development of new interventions are important for reducing violence and inequality. Fortunately, neurocognitive research and brain imaging research have found a correlation between antisocial or prosocial behavior and the prefrontal cortex. Recent brain stimulation research adopting transcranial direct current stimulation or transcranial magnetic stimulation has shown a causal relationship between brain regions and behaviors, but the findings are mixed. In the present study, we aimed to study whether stimulation of the DLPFC can change participants’ antisocial and prosocial behavior in the condition of inequality. We integrated antisocial and prosocial behavior in a unified paradigm. Based on this paradigm, we discussed costly and cost-free antisocial and prosocial behavior. In addition, we also measured participants’ disadvantageous and advantageous inequality aversion. The current study revealed an asymmetric effect of bilateral stimulation over the DLPFC on costly antisocial behavior, while such an effect of antisocial behavior without cost and prosocial behavior with and without cost were not observed. Moreover, costly antisocial behavior exhibited by men increased after receiving right anodal/left cathodal stimulation and decreased after receiving right cathodal anodal/left anodal stimulation compared with the behavior observed under sham stimulation. However, subjects’ inequality aversion was not influenced by tDCS.